Potential of Spirulina platensis as a feed supplement for poultry to enhance growth performance and immune modulation - El-Shall, Nahed A.; Jiang, Shouqun; Farag, Mayada R.; Azzam, Mahmoud; Al-Abdullatif, Abdulaziz A.; Alhotan, Rashed; Dhama, Kuldeep; Hassan, Faiz-ul; Alagawany, Mahmoud (Frontiers in Immunology, 2023)
Increase in drug resistance as well as ineffective immunization efforts against various pathogens (viruses, bacteria and fungi) pose a significant threat to the poultry industry. Spirulina is one of the most widely used natural ingredients which is becoming popular as a nutritional supplement in humans, animals, poultry and aquaculture. It contains protein, vitamins, minerals, fatty acids, pigments, and essential amino acids. Moreover, it also has considerable quantities of unique natural antioxidants including polyphenols, carotenoids, and phycocyanin. Dietary supplementation of Spirulina can beneficially affect gut microbial population, serum biochemical parameters, and growth performance of chicken. Additionally, it contains polyphenolic contents having antibacterial effects. Spirulina extracts might inhibit bacterial motility, invasion, biofilm formation, and quorum sensing in addition to acting directly on the bacterium by weakening and making the bacterial cell walls more porous, subsequently resulting in cytoplasmic content leakage. Additionally, Spirulina has shown antiviral activities against certain common human or animal viruses and this capability can be considered to exhibit potential benefits against avian viruses also. Spirulan, a calcium-rich internal polysaccharide of Spirulina, is potentially responsible for its antiviral effect through inhibiting the entry of several viruses into the host cells, boosting the production of nitric oxide in macrophages, and stimulating the generation of cytokines. Comparatively a greater emphasis has been given to the immune modulatory effects of Spirulina as a feed additive in chicken which might boost disease resistance and improve survival and growth rates, particularly under stress conditions. This manuscript reviews biological activities and immune-stimulating properties of Spirulina and its potential use as a dietary supplement in poultry to enhance growth, gut health and disease resistance.